PENGARUH KONSELING PERSONAL TERHADAP PERILAKU PENCEGAHAN PENULARAN TB PARU DI WILAYAH KERJA PUSKESMAS TIGO BALEH KOTA BUKITTINGGI - Tika Ramadanti; Syukra Alhamda; Sindi Sukma; Rahmi Kurnia Gustin (Universitas Fort De Kock, 2023)
Pulmonary Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. The bacteria can attack almost all organs of the human body, but most of them attack the lung organs. One way that can be used to prevent the transmission of pulmonary TB is health counseling carried out by counselors personally to reduce the high number of Pulmonary TB cases, at the tigo baleh health center in Bukitinggi City, 15 pulmonary TB patients were found. so there is a need for personal counseling to help pulmonary TB patients. The purpose of this study was to determine the effect of personal counseling on the behavior of preventing pulmonary TB transmission in the Tigo Baleh Health Center Work Area in Bukitinggi City. The research design uses a quasi-experimental design with a design one group pre-test post-test design approach method. The sample in this study was 15 respondents. The sampling technique is total sampling and the data collection technique used is a questionnaire. The data analysis method used is a paired t test using SPSS. The results of this study prove that more than half (61.5%) of respondents had bad lung TB transmission prevention behaviors before being given personal counseling and after being given personal counseling obtained the results of an average score (69.2%) with the category of having good behavior towards behaviors preventing pulmonary TB transmission. From the paired t-test, a p-value of 0.00 (< 0.05) was obtained, so it can be concluded that there is a personal counseling on the behavior of preventing pulmonary tb transmission to the behavior of preventing pulmonary tb transmission in the work area of the tigo baleh health center in bukitinggi city in 2022. It is hoped that subsequent researchers can conduct the same research using more samples